Microbial dynamics in rearing trials of Hermetia illucens larvae fed coffee silverskin and microalgae. (February 2021) - Osimani, Andrea; Ferrocino, Ilario; Corvaglia, Maria Rita; Roncolini, Andrea; Milanović, Vesna; Garofalo, Cristiana; Aquilanti, Lucia; Riolo, Paola; Ruschioni, Sara; Jamshidi, Elham; Isidoro, Nunzio; Zarantoniello, Matteo; et al.
Graphical abstract: Highlights: Hermetia illucens larvae were reared on coffee silverskin enriched with microalgae. Rearing substrates, larvae and frass were subjected to metataxonomic analysis. High counts of viable microorganisms were detected in all the analyzed samples. Lactobacillus, Leuconostoc and Weissella were present in the rearing substrates. An algae-mediated modulation of bacteria occurring in larvae and frass was suggested. Abstract: In the present study, Hermetia illucens larvae were reared on a main rearing substrate composed of a coffee roasting byproduct (coffee silverskin, Cs) enriched with microalgae ( Schizochytrium limacinum or Isochrysis galbana ) at various substitution levels. The microbial diversity of the rearing substrates, larvae, and frass (excrement from the larvae mixed with the substrate residue) were studied by the combination of microbial culturing on various growth media and metataxonomic analysis (Illumina sequencing). High counts of total mesophilic aerobes, bacterial spores, presumptive lactic acid bacteria, coagulase-positive cocci, and eumycetes were detected. Enterobacteriaceae counts were low in the rearing diets, whereas higher counts of this microbial family were observed in the larvae and frass. The microbiota of the rearing substrates was characterized by the presence of lactic acid bacteria, including the genera Lactobacillus, Leuconostoc and Weissella . The microbiota of the H. illucens larvae fed Cs was characterized by the dominance of Paenibacillus . H. illucens fed diets containing I. galbana were characterized by the presence of Enterococcus, Lysinibacillus, Morganella, and Paenibacillus, depending on the algae inclusion level, while H. illucens fed diets containing S. limacinum were characterized by high relative abundances of Brevundimonas, Enterococcus, Paracoccus, and Paenibacillus, depending on the algae inclusion level. Brevundimonas and Alcaligenes dominated in the frass from larvae fed I. galbana ; the predominance of Brevundimonas was also observed in the frass from larvae fed Schyzochitrium -enriched diets. Based on the results of the present study, an effect of algae nutrient bioactive substances (e.g. polysaccharides, high-unsaturated fatty acids, taurine, carotenoids) on the relative abundance of some of the bacterial taxa detected in larvae may be hypothesized, thus opening new intriguing perspectives for the control of the entomopathogenic species and foodborne human pathogens potentially occurring in edible insects. Further studies are needed to support this hypothesis. Finally, new information on the microbial diversity occurring in insect frass was also obtained.